Asuhan Keperawatan Pada Tn.K Dengan Post Operasi Herniotomi Di Ruang Anggrek RS Pandan Arang Boyolali - RATRIANTO, LILIK; , Arina Maliya, S.Kep., M.Si.Med (2015)
Background : Hernia Inguinalis Lateralis is Hernia which pass through Anulus Inguinalis/ Lateralis/ Internus and follow the way of spermatic cord in canalis inguinalis and can pass through annulus inguinalis subkutan (externus) to skrotum. Hernia Inguinalis often appears on male and more often in the right side. Un patient with post herniotomy operation found nursing problem. Aim of Researh: Able to do the assesment on post herniotomy operation's patient, maintain about the nursing diagnose on post herniotomy operation's patient, know the measure on post herniotomy operation's patient, know the measure evaluation which had done on post herniotomy operation's patient. Result : After nursing care had done for 3x24 hours can be found the result, patient's painful decrease from 6 become 1 scale, mobility disturbance, ansietas, and disturbance of less nutrition from nenessity on patient can be overcome. Conclusion : Diagnose which had found on post herniotomy operation's case in Mr. K is critical painful b.d agens physical injury (surgery incision), physical mobility disturbance , b.d painful restriction post operation, retraction of needlework trace, ansietas b.d change of sanitary status, less nutrition from body necessity b.d intake food which not adekuat, queasy post surgery. Keyword : Post Herniotomy Operation